Developing Self-Motivated, Empowered Middle School Students A Practical Solution Strategy - Friedman, Madeleine ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
Developing self-motivated, empowered middle school students is an ongoing struggle for teachers and administrators. This practicum was designed to address the problem teachers have in finding specific teaching strategies that would help students become empowered and self-motivated learners. This study focuses on directly integrating techniques with the presentation of academic content, rather than separate from that content. A booklet of 19 strategies was formulated and presented at a workshop with 6 participating teachers. The teachers were met with regularly during implementation, and meeting results were recorded. A pre/post checklist of intrinsically motivated behaviors in students was developed and administered to all participating teachers and students. Analysis of the data revealed that a successful workshop, by itself, did not ensure adequate transfer of teaching strategies. Regular postworkshop meetings for collegial support were not a substitute for a continuous program of modeling, coaching, and practice. Students as well as teachers needed a period of adjustment when new teaching strategies were implemented in the classroom. Sporadic use of new motivational strategies on an irregular basis, however well-meaning, were not enough to contribute to positive attitudinal changes in students. Fifteen appendices are attached, including a list of 19 strategies, check lists, and surveys and questionnaires. (4 tables) (68 references) (LAP)
ERIC Note: Ed.D. practicum report, Nova University.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Intermediate Grades; Junior High Schools; Learning Motivation; Middle School Students; Middle Schools; Motivation Techniques; Student Motivation; Teaching Methods; Dissertations/Theses, Practicum Papers; Tests/Questionnaires.